ChemInform Abstract: Synthesis and Applications of α‐Trifluoromethylated Alkylboron Compounds. Issue 17 (28th April 2014) - Argintaru, O. Andreea; Ryu, DaWeon; Aron, Ioana; Molander, Gary A.
Abstract The reaction of boron compounds with trifluoroethylidene affords bench‐stable trifluoromethylated organoboron compounds for the first time, which can be easily further converted [cf.